Vasa previa with velamentous cord insertion: a case report - Minchola Vega, Jorge Luis (2023)
Vasa previa is a rare and infrequent prenatal finding of hemorrhage in the secondhalf of pregnancy, in which umbilical vessels devoid of Wharton's jelly interposebetween the fetal presentation and the internal cervical os. When undetected andrupture of the vessels occurs, it is associated with a high perinatal mortality rate.Three types are described; the case presented is type 1 vasa previa secondary tovelamentous insertion of the cord. It was diagnosed prenatally by transvaginalultrasound associated with color Doppler. A cesarean section was performed withfavorable maternal and perinatal evolution